Reference Echovirus 7 and 19 Genomes from Nigeria (2018)
We describe the genomes of two echovirus isolates from Nigeria as reference enterovirus species B genomes for the region. These echovirus 7 and 19 genomes have 7,411 nucleotides (nt) and 7,426 nt and were recovered from sewagecontaminated water (in 2010) and an acute flaccid paralysis case (in 2014), respectively.